Analysis of the Message of Preaching in the Meaning of the Symbols of the SigehPengunten Dance - Agustin, Mae Sella; Muhajir, Muhajir; Kurniawan, Siroy (UIN Fatmawati Sukarno Bengkulu, 2024)
Da'wah does not always have to talk about Islam but the essence of da'wah itself is to convey good things, but it cannot be separated from religious beliefs. The goal to be achieved in this study is to find out the da'wah message contained in the SigehPengunten Dance art. The method in this study is qualitative. The type of library research .This study is descriptive qualitative. Data collection techniques used are documentation, interviews, observations. This study uses the Triangulation data validity technique. The data analysis used is the Miles and Huberman model data analysis where data is collected, reduced, presented and conclusions or verification are drawn. Data processing in this study uses Charles Sanders Peirce's theory analysis.Based on the results of the research conducted by researchers on